2007
DOI: 10.3177/jnsv.53.556
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Down-Regulates the Androgen Receptor at the Post-Translational Level in Prostate Cancer Cells

Abstract: Summary Androgen receptor (AR) functions as a transcriptional factor for the development and progression of prostate cancer. Resveratrol is known to inhibit the function of AR and to repress AR expression at the transcriptional level. This study focuses on the effects of resveratrol on the AR function and the post-translational AR level. Resveratrol repressed the transcriptional activities of a mutant AR lacking the ligand-binding domain, a constitutive active form of AR, and wild-type AR in a concentration-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 22 publications
5
41
0
Order By: Relevance
“…1,2 Resveratrol inhibits cancer cell growth in many cell lines, including cancers of the lung, prostate, colon, breast and ovaries. [3][4][5][6][7][8][9][10][11][12][13][14] Resveratrol also reduces tumor incidence in animal models by interfering with carcinogenesis through a wide array of anti-cancer actions. Several animal studies have demonstrated the ability of resveratrol to inhibit prostate cancer development by downregulating androgen receptors, inducing apoptosis/cell cycle arrest and inhibiting disease progression.…”
mentioning
confidence: 99%
“…1,2 Resveratrol inhibits cancer cell growth in many cell lines, including cancers of the lung, prostate, colon, breast and ovaries. [3][4][5][6][7][8][9][10][11][12][13][14] Resveratrol also reduces tumor incidence in animal models by interfering with carcinogenesis through a wide array of anti-cancer actions. Several animal studies have demonstrated the ability of resveratrol to inhibit prostate cancer development by downregulating androgen receptors, inducing apoptosis/cell cycle arrest and inhibiting disease progression.…”
mentioning
confidence: 99%
“…Till to date, multidirectional studies attempting to unravel the biochemical basis of chemoprevention and chemotherapy with resveratrol have revealed that the compound (i) prevents the activation of various carcinogens, (ii) protects cellular macromolecules from oxidative damage, (iii) activates the carcinogen detoxification pathways, (iv) attenuates inflammatory responses, (v) inhibits proliferation of cancer cells, (vi) induces apoptosis selectively in cancer cells, (vii) impedes the angiogenic and metastatic progression, and (viii) enhances the sensitivity of cancer cells to conventional chemotherapy and radiotherapy (Kundu and Surh, 2008). Previous studies have demonstrated that resveratrol inhibits the proliferation and induces apoptosis in various prostate cancer cells (Mitchell et al, 1999;Narayanan et al, 2003;Harada et al, 2007). Resveratrol attenuated the growth of prostate tumors in a transgenic rat adenocarcinoma of prostate (TRAMP) model.…”
Section: Discussionmentioning
confidence: 99%
“…Biomol Ther 22(5), 426-430 (2014) www.biomolther.org that resveratrol attenuates the proliferation of LNCaP prostate cancer cells by downregulating AR protein expression following transcriptional (Mitchell et al, 1999) or post-translational (Harada et al, 2007) mechanisms. However, a molecular link between the inhibitory effect of resveratrol on STAT3 signaling and the downregulation of AR has not been established.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…We have found that resveratrol inhibits AR transactivation without binding to the LBD of AR. 13) We also found that resveratrol inhibited the N-C interaction of AR in human prostate cancer PC-3 cells (N. Harada, unpublished data). Taken together, our data indicate that the N-C/ -catenin system can detect not only androgenic and anti-androgenic compounds that bind to the LBD of AR, but also compounds that inhibit the N-C interaction in ways that do not involve binding to the LBD.…”
mentioning
confidence: 90%